Pe Pengaruh Pojok Baca dalam Meningkatkan Minat Membaca dan Hasil Belajar Bahasa Indonesia siswa kelas IV di SDN Baru 07 Pagi: EFFECT OF READING CORNER IN INCREASING INTEREST IN READING AND LEARNING OUTCOMES OF INDONESIAN LANGUAGE CLASS IV STUDENTS AT SDN BARU 07 MORNING JAKARTA EAST - Anti, Putri Rianti (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Putri Rianti. NIM : 1901025092. The effect of reading corners in increasing reading interest and Indonesian language learning outcomes in fourth grade students at SDN Baru 07 Pagi East Jakarta Jakarta: Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University Prof. Dr. Hamka, June 2023This study aims to determine the effect of reading corners on reading interest and Indonesian language learning outcomes in fourth grade students at SDN Baru 07 Pagi, East Jakarta. This type of research is associative quantitative. The research population was all fourth grade students at SDN Baru 07 Pagi, consisting of 60 students. The sample determination was carried out using a purposive sampling technique, so that 30 students from each class IV and IV B totaled 15 students. Data on reading interest was collected using a questionnaire and Indonesian language learning outcomes using the results of Indonesian language report cards in semester 1 of the 2022/2023 academic year. Data were analyzed using validity test analysis, instrument reliability test, descriptive statistics, prerequisite test; normality test, homogeneity test, and hypothesis testing using the t-test and simple regression test. The analysis test was carried out with the help of excel and SPSS 24 for windows. The results showed that: there was a significant positive effect between reading corners on reading interest and Indonesian language learning outcomes in fourth grade students at SDN Baru 07 Pagi East Jakarta. Keywords: Reading corner, reading interest, Indonesian learning outcomes